Screening the east : Heimat, memory and nostalgia in German film since 1989 - Hodgin, Nick (Film Europa, 2011)
" ... contains useful and nuanced readings of the best-known films dealing with themes related to unification, as well as highlighting some equally interesting lesser-known works, in order to provide a rounded picture of German cinema's engagement with these issues in the past 17 years. I am not aware of any other publication that covers such a range of material and this in itself makes the book a valuable contribution to the field." * David Clarke, University of Bath "This is an extremely rich study of the representation of east German identity and the former GDR in post-unificat.